The wage impact of immigration in Germany: New evidence for skill groups and occupations - Max Friedrich Steinhardt (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2009)
The paper contributes to the ongoing debate about the adequate technique to identify the impact of immigration. Initially the regression analysis on the basis of education-experience cells reveals that the impact of immigration on native wages in Germany is negative, but small. The subsequent analysis on the basis of occupations using the same data yields a considerably higher adjustment coefficient and indicates strong wage effects within primary service occupations with a magnitude comparable to results for the US. The analysis therefore demonstrates that the use of formal qualifications as an exclusive classification criterion may lead to an underestimation of the impact of immigration.
Keywords: C23; J15; J31; J42; J60; 330; Labour market impact of migration; skill group approach; occupations; fixed effects model